2018
DOI: 10.1002/pep2.24059
|View full text |Cite
|
Sign up to set email alerts
|

Covalent conjugation of cationic antimicrobial peptides with a β‐lactam antibiotic core

Abstract: To combat the serious issue of increasing global antibiotic resistance, new antimicrobial therapies are urgently required. As one alternative, previously used antibiotics are being investigated for use in combination with more modern antibiotics including antimicrobial peptides. Towards this goal, 7‐aminocephalosporanic acid, the precursor to the conventional β‐lactam antibiotic, cephalosporin, and the related compound, 7‐aminodesacetoxycephalosporanic acid, were each chemically modified to enable their use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Peptides Indolicidin [80] 16 32 CAMA a [12] 4 -Nisin [12] 8 -A3-APO [89] Not effective 13 Cecropin P1 [70] -16-32 (and 4 d ) Chex1-Arg20 [89] Not an increase in the antimicrobial action [84]. Methods of conjugating peptides with antibiotics depend on the structures of both but include utilizing amide bond formation attached to linking group [85], a disulfide tether [86] and a glutaraldehyde linker [87].…”
Section: Gram Negative Mic (Mg/l) E Coli Atcc 25922 or E Coli (Wildmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptides Indolicidin [80] 16 32 CAMA a [12] 4 -Nisin [12] 8 -A3-APO [89] Not effective 13 Cecropin P1 [70] -16-32 (and 4 d ) Chex1-Arg20 [89] Not an increase in the antimicrobial action [84]. Methods of conjugating peptides with antibiotics depend on the structures of both but include utilizing amide bond formation attached to linking group [85], a disulfide tether [86] and a glutaraldehyde linker [87].…”
Section: Gram Negative Mic (Mg/l) E Coli Atcc 25922 or E Coli (Wildmentioning
confidence: 99%
“…As solid phase synthesis of peptides can produce an amidated terminus on the peptide, using this to link the peptide to a drug is logical [88]. The covalent conjugation of the cationic AMP, Chex1-Arg20, and several other AMPs, including the magainin analogue MSI-78 with 7-cephalosporanic acid and/or 7-aminodesacetoxycephalosporanic acid, was undertaken by Li et al [89]. This was achieved by attaching the 7-amino group of cephalosporin to the N-terminus of the peptide.…”
Section: Gram Negative Mic (Mg/l) E Coli Atcc 25922 or E Coli (Wildmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs have also been linked to conventional β‐lactam antibiotics, and their corresponding conjugates have been shown to enhance the antibacterial activity of their parent drugs. For example, Li et al recently reported the conjugation of functionalized 7‐aminocephalosporanic acid (7‐ACA; 62 ) and 7‐aminodesacetoxycephalosporanic acid (7‐ADCA; 63 ) with MSI‐78 ( 64 ), a synthetic from the magainin analog family (Figure ). In fact, ( 64 ) (a cationic AMP with sequence: GIGKFLKKAKKFGKAFVKILKK‐NH 2 ) previously showed a synergic effect in vitro against bloodstream infections when combined with β‐lactam antibiotics .…”
Section: Trojan Horse Approaches To Overcome Antimicrobial Resistancementioning
confidence: 99%
“…In fact, ( 64 ) (a cationic AMP with sequence: GIGKFLKKAKKFGKAFVKILKK‐NH 2 ) previously showed a synergic effect in vitro against bloodstream infections when combined with β‐lactam antibiotics . In the report by Li and his co‐workers, ( 62 ) and ( 63 ) were chemically modified to enable their use in solid phase peptide synthesis for covalent conjugation via their 7‐amino group and a glycolic linker to the N ‐terminus of ( 64 ) to create the conjugates ( 65 ) and ( 66 ), respectively (Figure ). The obtained MSI‐78‐β‐lactam conjugates were evaluated for antibacterial activity against a panel of six Gram‐negative pathogens, including clinically isolated MDR strains (Table ).…”
Section: Trojan Horse Approaches To Overcome Antimicrobial Resistancementioning
confidence: 99%